Research on the ecological–economic effects of combined planting–breeding modes: a case study of Zizania latifolia–shelduck in China - Wangtengfei Teng; Lidan Xu; Zhidong Li; Moucheng Liu; Didi Rao; Qi Wan (Frontiers in Sustainable Food Systems)
In the context of global climate change, it is crucial to adopt ecologically sound production practices to promote sustainable agricultural development. Combined rice–fish, rice–crab, and Zizania latifolia (ZL)–shelduck modes are increasingly advocated by scholars because of the complex farmland landscapes and environmentally friendly nutrient cycles associated with these modes. In this study, a comprehensive evaluation of the ecological–economic benefits of a combined planting–breeding system in Jinyun, Zhejiang, China, was conducted via life cycle assessment (LCA) and cost–benefit analysis on the basis of literature review and field research data. The following results were obtained. (1) The single-season total carbon footprint for the combined ZL–shelduck planting–breeding mode was 4062.19 kg CO2 eq/ha, whereas it was 4553.32 kg CO2 eq/ha for the ZL monoculture mode. Compared with those of the ZL monoculture mode, the carbon emissions of the combined ZL–shelduck mode decreased by 10.79%, with agricultural inputs identified as the primary source of carbon emissions for both modes. (2) The net ecological and economic benefits of the combined planting–breeding mode and the monoculture mode were 102,482.26 yuan/ha and 70,423.60 yuan/ha, respectively. Compared with those of the ZL monoculture mode, the net benefits significantly increased by 45.52% in the combined planting–breeding mode. Notably, the sale of shelduck products and reductions in agricultural inputs and labor costs were important factors leading to the income gap between the two types of modes. This study not only provides a quantitative evaluation of the comprehensive ecological–economic benefits of different agricultural production modes but also serves as an important reference for the introduction of relevant ecological compensation policies and the promotion of production and ecological win–win in the future.